Foxg1 Is Required for Morphogenesis and Histogenesis of the Mammalian Inner Ear - Pauley, Sarah (2006)
The forkhead genes are involved in patterning, morphogenesis, cell fate determination, and proliferation. Several Fox genes (Foxi1, Foxg1) are expressed in the developing otocyst of both zebrafish and mammals. We show that Foxg1 is expressed in most cell types of the inner ear of the adult mouse and that Foxg1 mutants have both morphological and histological defects in the inner ear. These mice have a shortened cochlea with multiple rows of hair cells and supporting cells. Additionally, they demonstrate striking abnormalities in cochlear and vestibular innervation, including loss of all crista neurons and numerous fibers that overshoot the organ of Corti. Closer examination shows that some anterior crista fibers exist in late embryos. Tracing these fibers shows that they do not project to the brain but, instead, to the cochlea. Finally, these mice completely lack a horizontal crista, although a horizontal canal forms but comes off the anterior ampulla. Anterior and posterior cristae, ampullae, and canals are reduced to varying degrees, particularly in combination with Fgf10 heterozygosity. Compounding Fgf10 heterozygotic effects suggest an additive effect of Fgf10 on Foxg1, possibly mediated through bone morphogenetic protein regulation. We show that sensory epithelia formation and canal development are linked in the anterior and posterior canal systems. Much of the Foxg1 phenotype can be explained by the participation of the protein binding domain in the delta/notch/hes signaling pathway. Additional Foxg1 effects may be mediated by the forkhead DNA binding domain.